JAMINAN KESEHATAN NASIONAL PERSPEKTIF MASLAHAT MUADALAH DAN SIYASAH SYARIAH - Muhammad Nafi; Mohammad Sahli Ali; Muh. Arief Budiman; Muhammad Sholah Ulayya (Siyasah Wa Qanuniyah, 2024)
This article aims to highlight the choice of health insurance fiqh that has been legally binding in the presence of MUI DSN-MUI Fatwa Number 98/DSN-MUI/XII/2015 concerning Guidelines for the Implementation of Sharia Health Social Security. This research examines the concept of maslahat muadalah (maslahat keadilan) and siyasah sharia, which are realized to introduce the fiqh of health insurance offered in an effort to provide an alternative to fiqh for the Indonesian Muslim community related to this BPJS Kesehatan fiqh. This research is library research, whose data source is taken from books, journals, and another research. The result of this study is that, from the reconstruction of JKN fiqh using the theories of maslahat muadalah and siyasah sharia, it was found that if the state has promulgated a regulation that contains maslahah muadalah even though it is a disputed fiqh, then the community is still obliged to follow and comply with it. If there is a conflict between the content of the regulatory material and the existing fiqh rules, a judicial review of the regulation should be submitted.